Avicenna's Logic of Ethics - Tayyebeh Ahmadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article deals with the logic of ethical propositions, i.e. the reason for the integrity of ethical rules from Avicenna's point of view. It begins with the consideration of Ara-e Mahmoudeh (accepted norms), the philosopher's first and most famous keyword, which describes the essence of ethics and explains the reason for its observance in a person's life. Considering Avicenna's logic of ethics and through critical analysis, two new conclusions can be stated: 1) Avicenna's ethics is compatible with contemporary evolutionary explanations of ethics due to its non-platonic character, practicality and minimal rationality. 2) The path taken by Avicenna in his book